The role of business leadership in uplifting the local communities in mining areas: a South African perspective in the globalisation era - Kanjere, Maria Matshidiso (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
The interconnectedness of economies due to globalisation makes it difficult for companies, especially in Africa to have a local developmental perspective. This is due to volatile markets and the desires of companies to acquire more market shares and in the process strengthen their share prices. This is done so as to generate more revenues for the share-holders and create wealth for the minority population that is more often than not, not even residing in Africa. Thus, the focus of business leadership in Africa has to be more on corporate social responsibility as opposed to the focus of other business leaders in most developed countries, who exploit African resources to benefit their own countries. Many developed countries are not faced with the challenges of poverty, poor health systems and high unemployment rate as it is the case in most African countries. In South Africa, many communities residing next to the mines are economically still disadvantaged. This is despite a number of legislation and policies, including the mining charters that are meant to encourage the business leadership in the mining sector to contribute to the well-being of the society. Thus, the focus of this paper is on business leadership in the mining sector. Business leadership has failed many societies by contributing as little as they can on developing local economies. Hence, many societal members are disgruntled with the failure of government to enforce certain legislation and policies that are meant to empower communities economically. Furthermore, communities are angry at mining leadership that does not deliver on substantial benefits. The persistent ignorance of business leadership in African countries, especially in South Africa, to develop local communities result in a number of community protests which unfortunately vandalise the little resources that the communities have. Therefore, this paper argues that business leadership in South Africa has to play a transformative role that will enhance the socio-economic livelihood of communities residing in the mining areas.
Journal article, Published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: Socio-economic factors; Globalisation; Corruption; Social responsibility of business; Globalization -- Economic aspects -- South Africa